Evolution of the integrin ? and ? protein families. - Hughes, A.L. (Journal of Molecular Evolution, 2001)
A phylogenetic analysis of vertebrate and invertebrate alpha integrins supported the hypothesis that two major families of vertebrate alpha integrins originated prior to the divergence of deuterostomes and protostomes. These two families include, respectively, the alpha PS1 and alpha PS2 integrins of Drosophila melanogaster, and each family has duplicated repeatedly in vertebrates but not in Drosophila. In contrast, a third family (including alpha PS3) has duplicated in Drosophila but is absent from vertebrates. Vertebrate alpha PS1 and alpha PS2 family members are found on human chromosomes 2, 12, and 17. Linkage of these family members may have been conserved since prior to the origin of vertebrates, and the two genes duplicated simultaneously. A phylogenetic analysis of beta integrins did not clearly resolve whether vertebrate beta integrin genes duplicated prior to the origin of vertebrates, although it suggested that at least the gene encoding vertebrate beta 4 may have done so. In general, the phylogeny of neither alpha nor beta integrins showed a close correspondence with patterns of alpha--beta heterodimer formation or other functional characteristics. One major exception to this trend involved alpha L, alpha M, alpha X, and alpha D, a monophyletic group of immune cell-expressed alpha integrins, which share a number of common functional characteristics and have evolved in coordinated fashion with their beta integrin partners.